OPTIMIZATION OF KOTO JAYA DAILY MARKET PRODUCTION IN MUKOMUKO - Yoki Kurniawan; Rahmat Al Hidayat (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This study aims to identify internal and external factors faced by the Koto Jaya Daily Market in Mukomuko, determine the optimization strategy of the market utilization. The data used in this study are primary data obtained from traders at the Koto Jaya Daily Market in Mukomuko in 2018 using a SWOT analysis tool.The results of the SWOT analysis can be concluded that internal factors in optimizing the utilization of the Koto Jaya Daily Market in Mukomuko are; 1) Strength Factors (land availability, location, supporting facilities, trader organizations, merchant composition, infrastructure, price information); 2) Weakness factors (rental prices, utilities, location access, market conditions, budget constraints, trader awareness), for external factors in optimizing the utilization of the Koto Jaya Daily Market in Mukomuko are; 1) Opportunity factors (population, community response, government support, technological development); 2) Threat factors (other market competitors, natural disasters, thuggery, government policies, economic crisis). The strategy that must be applied in this condition is the WT (Weaknesses-Threats) strategy, namely; 1) Implement a kiosk and booth rental price strategy; 2) Improve the quality and service quality of the Koto Jaya Mukomuko Market; 3) Optimizing existing facilities and infrastructure; 4) Maintain market security and comfort